2012
DOI: 10.1016/j.mce.2011.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Actions of estrogens and endocrine disrupting chemicals on human prostate stem/progenitor cells and prostate cancer risk

Abstract: Estrogen reprogramming of the prostate gland as a function of developmental exposures (aka developmental estrogenization) results in permanent alterations in structure and gene expression that leads to an increased incidence of prostatic lesions with aging. Endocrine disrupting chemicals (EDCs) with estrogenic activity have been similarly linked to an increased prostate cancer risk. Since it has been suggested that stem cells and cancer stem cells are potential targets of cancer initiation and disease manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 117 publications
(135 reference statements)
0
73
1
Order By: Relevance
“…This suggests that the genetic and environmental factors, including the diet and behavior, may influence the PC development [12,13] . Importantly, a growing body of evidence has also revealed that the accumulation of genetic and epigenetic alterations in prostate stem/progenitor cells and their differentiated progenies concomitant with the changes in their local microenvironment, including in reactive stromal cells, may occur during severe injury, inflammation, oxidative stress and aging of the prostate gland and lead to PC development ( Figures 1 and 2) [6,7,[14][15][16][17][18] . Moreover, it has been shown that PC stem/progenitor cells and their differentiated progenies can acquire more malignant phenotypes during epithelial-mesenchymal (EMT) program and PC progression to locally invasive and metastatic CRPCs [6,17] .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the genetic and environmental factors, including the diet and behavior, may influence the PC development [12,13] . Importantly, a growing body of evidence has also revealed that the accumulation of genetic and epigenetic alterations in prostate stem/progenitor cells and their differentiated progenies concomitant with the changes in their local microenvironment, including in reactive stromal cells, may occur during severe injury, inflammation, oxidative stress and aging of the prostate gland and lead to PC development ( Figures 1 and 2) [6,7,[14][15][16][17][18] . Moreover, it has been shown that PC stem/progenitor cells and their differentiated progenies can acquire more malignant phenotypes during epithelial-mesenchymal (EMT) program and PC progression to locally invasive and metastatic CRPCs [6,17] .…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that AR downregulation by GDNF signaling may lead to partial androgen insensitivity in the developing prostate. This is an intriguing hypothesis because disruption of AR-mediated prostate development predisposes humans and rodents to prostate neoplasia by altering the phenotype of the gland early in life (Anway and Skinner, 2008;Gupta, 2000;Ho et al, 2006;Hu et al, 2012;Prins et al, 2014Ramos et al, 2001;Timms et al, 2005). Consistent with Ar being a GDNF-repressed gene, and Gdnf and Gfra1 being androgen- repressed genes in the UGS and developing prostate (Fig.…”
Section: Molecular Effectors Of Proliferation In the Ugs During Andromentioning
confidence: 83%
“…Androgen receptor (AR) signaling is required for prostate development (Cunha and Chung, 1981;Cunha and Lung, 1978;Donjacour and Cunha, 1988;Lasnitzki and Mizuno, 1980), and disruption of AR-mediated prostate development predisposes humans and rodents to prostate neoplasia by altering the phenotype of the gland early in life (Anway and Skinner, 2008;Gupta, 2000;Ho et al, 2006;Hu et al, 2012;Prins et al, 2014Ramos et al, 2001;Timms et al, 2005). Testosterone and its potent metabolite 5α-dihydrotestosterone (DHT) activate the AR during prostate development.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanisms are not fully understood. Although there is still no direct evidence that estrogens initiate PC in humans, there is accumulating evidence pointing towards a central role for estrogens in PC [89]. To give just some examples are the rising E2:T ratio in aging men, association of estrogen metabolizing gene polymorphisms and elevated urine hydroxy-estrone ratios with higher PC risk, progressive increase in aromatase expression in PCs upon advancement to metastatic disease, and marked alterations in estrogen receptor expression with cancer progression.…”
Section: Advances In Prostate Cancermentioning
confidence: 99%